A Randomized, Placebo‐Controlled Trial of Transdiscal Radiofrequency, Biacuplasty for Treatment of Discogenic Lower Back Pain. Issue 3 (28th December 2012) - Kapural, Leonardo; Vrooman, Bruce; Sarwar, Sheryar; Krizanac‐Bengez, Ljiljana; Rauck, Richard; Gilmore, Christopher; North, James; Girgis, Girgis; Mekhail, Nagy
Abstract Objective. The aim was to compare the efficacy of intradiscal biacuplasty (IDB) with that of placebo treatment for discogenic low back pain. Design. This is a randomized, placebo‐controlled trial. Subjects were randomized on a 1:1 basis to IDB and sham groups. Follow‐ups were conducted at 1, 3, and 6 months. Subjects and coordinators were blinded to randomization until 6 months. Of the 1, 894 subjects screened, 64 subjects were enrolled, and 59 were treated: 29 randomized to IDB and 30 to sham. All subjects had a history of chronic low back pain for longer than 6 months. Interventions. Two cooled radiofrequency (RF) electrodes placed in a bipolar manner in affected discs to lesion the nociceptive fibers of the annulus fibrosus. The sham procedure was identical to the active treatment except that probes were not directly inserted into the disc space, and RF energy was not actively delivered. Results. The principal outcome measures were physical function, pain, disability, and opioid usage. Patients in the IDB group exhibited statistically significant improvements in physical function (P = 0.029), pain (P = 0.006), and disability (P = 0.037) at 6‐month follow‐up as compared to patients who received sham treatment. Treatment patients reported a reduction of 16 mg daily intake of opioids at 6 months; however, the results were not statistically different from sham patients. Conclusions. The results suggest that the clinical benefits observed in this study are the result of non‐placebo treatment effects afforded by IDB. IDB should be recommended to select the patients with chronic discogenic low back pain. (Clinicaltrials.gov number, NCT00750191.)